Dare to matter : your path to making a difference now - Kassalow, Jordan S; Krause, Jennifer (Citadel Press/Kensington Publishing Corp., 2019)
We all want to make the world a better place, but with busy, demanding lives, most of us struggle with the where, when, and how. Dr. Jordan Kassalow, founder of VisionSpring, the groundbreaking venture that has restored eyesight and hope to millions of people across the globe, has the answers: here, now, and in your own way. Sharing his personal story of integrating real-world responsibilities with his desire to make a difference, Jordan offers you a practical way forward, custom-made for your unique talents and circumstances, to take you from thought to action. By exploring key questions about your strengths and interests, personal resources, core beliefs, and most cherished values, Jordan will give you the motivation and the tools to start repairing the world in a way that is meaningful, fulfilling, and true to you. He will show you how working to create change in the lives of others can have a positive impact on your own outlook, well-being, and quality of life. In a world awash in need, it's easy to give in to anger, frustration, and powerlessness, to let cynicism consume your natural optimism and hunger to build a better world. The soulful and pragmatic approach in this remarkable book will help you see with your heart and use your head to invest in your highest goals--while still earning a paycheck, being there for those you love, and enjoying life. To dare to matter, today.